2020
DOI: 10.1016/j.jup.2020.101057
|View full text |Cite
|
Sign up to set email alerts
|

Does public ownership of utilities matter for local government water policies?

Abstract: What differentiates local governments that implement water policies on equity and the environment? Analyzing a 2015 national survey of 1,897 U.S. municipalities, we find municipalities that own their water utilities are more likely to report policies to protect low-income residents from disconnection and implement water resource management. Respondents from 8% of municipalities report protecting residents from disconnection. State economic regulation of municipally owned utilities and Democrat-majority municip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 53 publications
0
21
0
1
Order By: Relevance
“…However, prior to the COVID-19 pandemic, mechanisms for ensuring water access, such as temporary bans on disconnections for low-income residents in the United States, were few ( Hauter and Grant, 2018 ). A national study using survey data from 2015 found only eight percent of responding municipalities protected low-income households from disconnection ( Homsy and Warner, 2020 ). The lack of universal service obligations and disconnection protections in the United States stands in stark contrast to Europe, where countries implement a variety of mechanisms to ensure access to water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prior to the COVID-19 pandemic, mechanisms for ensuring water access, such as temporary bans on disconnections for low-income residents in the United States, were few ( Hauter and Grant, 2018 ). A national study using survey data from 2015 found only eight percent of responding municipalities protected low-income households from disconnection ( Homsy and Warner, 2020 ). The lack of universal service obligations and disconnection protections in the United States stands in stark contrast to Europe, where countries implement a variety of mechanisms to ensure access to water.…”
Section: Introductionmentioning
confidence: 99%
“…Partisan political control could affect the decision of a state to impose a moratorium, as prior research has found that Republican-controlled governments are less likely to protect low-income consumers from water disconnection ( Homsy and Warner, 2020 ). We create a variable, unified Republican control, for states where both the state legislature and the Governor's office are Republican.…”
Section: Introductionmentioning
confidence: 99%
“…This may be because publicly owned utilities have a broader interest beyond profit; they are generally interested in fair pricing and affordability to their residents (Mann & Warner 2019;McDonald 2018). Municipally owned utilities are also more likely to protect low-income residents from water shutoff (Homsy & Warner, 2020;Warner et al 2020). Regarding problems with water affordability, private ownership and poverty rate are the primary drivers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study of Philadelphia's Tiered Assistance Program found that affordability programs based on household income in the US do not have a negative effect on water conservation efforts (Mack, et al 2020). A national study of US municipalities found that municipally owned systems were more likely to both impose conservation practices and protect consumers from water shut off (Homsy & Warner 2020). Some cities across the US have brought privatized systems back under public control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation